2022
DOI: 10.3390/foods11020143
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Partial Replacements of NaCl by KCl on Quality Characteristics and the Heterocyclic Aromatic Amine Contents of Bacon

Abstract: The influence of partial replacements of NaCl by KCl (0, 10, 20, and 30%) on the heterocyclic aromatic amine (HAAs) contents and quality characteristics of bacon were investigated. The Na+ content, moisture, aw, pH, L* value, and sensory saltiness decreased and K+ content, a* value, and sensory bitterness increased significantly with increased substituting rates of NaCl by KCl (p < 0.05). There were no significant differences between the control and KCl substitution samples for the b* value, redness, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Du et al . (2022) found that with the increase in the KCl replacement ratio, the content of TBARS in bacon increased, which might be due to the change in ionic strength caused by the substitution of the salt in the bacon sample. Yeşilsu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Du et al . (2022) found that with the increase in the KCl replacement ratio, the content of TBARS in bacon increased, which might be due to the change in ionic strength caused by the substitution of the salt in the bacon sample. Yeşilsu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Du et al . (2022) found that a high‐substitution rate of KCl increased the heterocyclic aromatic amine content and changed the quality of bacon. Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The carbonyl group content might be correlated with protein degradation, but it also strongly depended on the endogenous enzymes surrounding the groups. It has also been reported that the K + can facilitate more slack protein structures, further accelerating the oxidation of muscle protein [ 27 ]. Some water-soluble cellular substances were released from the sample as affected by KCl replacements, which might include antioxidant enzymes and other antioxidants, and this thus affected the oxidative stability of the sample [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The creatine contents of bacon were determined based on the methods of our previous work [ 25 ]. The results were presented as mg/g of dry matter of fried and unfried bacon (control).…”
Section: Methodsmentioning
confidence: 99%